Preliminary studies on selection of a vaccine candidate of Classical Swine Fever Virus - RAMESH, A; KUMANAN, K (The Indian Journal of Animal Sciences, 2023)
Classical swine fever is an economically important and endemic disease of swine in India. Though vaccination is the best way of controlling the disease, currently available vaccines are not very effective. Cell culture adapted local strains of viral pathogens could be a better choice for large scale vaccine production and better immunity. Two local isolates and one lapinized strain of Classical swine fever virus were adapted to PK-15 cells and assessed for their suitability as a vaccine candidate. The CSFV isolate, CSFV-Ind-TN/Veng-09-020–Vn, with a TCID50 titre of 9.5 after 40 continuous passages was found to give better seroconversion, good protection against virulent CSFV challenge and could be a better candidate vaccine strain.